Potensi Galur Padi Gogo di Lahan Kering Pulau Belitung - Mustikarini, Eries Dyah; Prayoga, Gigih Ibnu; Santi, Ratna; Aprilla, Nisriina Nur (Universitas Sebelas Maret, 2024)
Drought-tolerant upland rice varieties are important to support increased rice production. These varieties must be resistant to biotic and abiotic stress and have high yield. Testing the potential of lines on dry, acid land to measure adaptability and yield. This study aims to determine the yield and determine the highest yielding line of F8 upland rice. This research was conducted from August 2022 to April 2023 in Air Rayak Village, Tanjungpandan District, Belitung Regency. This research was conducted using an experimental method with a randomized block design (RBD). The treatment consisted of 5 F8 lines consisting of 19I-06-09-23-03, 21B-57-21-21-23, 23F-04-10-18-18, 23A-56-20-07-20 and 23A -56-22-20-05 and 5 check varieties consisting of Inpago 8, Inpago 12, Rindang 1, Danau Gaung and PBM UBB 1. Data analysis used the Fisher test (ANOVA) followed by the LSI (Least Significant Increase) follow-up test. The results all lines and varieties tested were able to grow and produce in Belitung Ultisols. The yield of the F8 lines on ultisols in Belitung Regency ranged from 2.00-4.54 kg/plot. The F8 lines that had the highest yield was the 23A-56-20-07-20 line, which was 4.54 kg/plot (white rice paddy) and the 23A-56-22-20-05 line, which was 2.14 kg/plot (brown rice paddy).